Sanctuary of the Lord of Miracles, Nuevo San Juan - Maria Campoverde:::photographer::: (2025)
Photo caption, written by Maria Campoverde: 'The Sanctuary of the Lord of Miracles viewed from the balcony of my house in San Juan Nuevo. This is the sanctuary that was built to replace the original building that was destroyed by the Paricutin volcano. The volcano erupted in 1943 and destroyed our original town and church.'